Commemorative Palimpsests in Post-Authoritarian Argentina: The Case of ESMA - Emily R Nelsen (Vernacular: New Connections in Language, Literature, & Culture, 2023)
The authoritarian military regime in Argentina (1976-1983) left lasting impacts on the country’s social, political, and economic way of life. Characterized by thousands of violations of human rights, this period in history is still felt in Argentine society as activists and families search for truth. Simultaneously, other actors prefer to deny responsibility and argue for the need to move on, thus renouncing the legacy of state terror. ESMA, a notorious former clandestine torture center in Buenos Aires, became a site of memory on March 24, 2004, a date that also came to symbolize the anniversary of the coup d’état. Using the case study of ESMA, my research into how four Argentine presidential administrations since 1989 have commemorated the anniversary of the dictatorship on March 24 will investigate the following issues: 1) How did political leaders influence the cultural prominence of ESMA? 2) As a physical reminder of past conflict, how have commemorative events at ESMA generated new rounds of conflict in each presidential term? By answering these questions, this paper will contribute to the understanding of how the initiatives of different political administrations shaped and will continue to influence Argentina’s search for closure amidst the commemoration of the country’s past.
Keywords: post-authoritarianism in Argentina; politics of memory; human rights; trauma